To solve the equation \((x - 1)(2x + 5) = 0\) using the Zero Product Property, we set each factor equal to zero and solve for \(x\):
-
\(x - 1 = 0\)
- Adding 1 to both sides gives: \[ x = 1 \]
-
\(2x + 5 = 0\)
- Subtracting 5 from both sides gives: \[ 2x = -5 \]
- Dividing both sides by 2 gives: \[ x = -\frac{5}{2} \]
Thus, the values of \(x\) that make the quadratic equation equal zero are: \[ x = 1 \quad \text{and} \quad x = -\frac{5}{2} \]
The correct response is: The quadratic equation will equal zero when x equals negative Start Fraction 5 over 2 End Fraction and x equals 1.